AKUNTABILITAS DAN TRANSPARANSI DALAM PENGELOLAAN DANA DESA LAGADING MASA PANDEMI COVID 19 - Nurhatifa Nurhatifa; Muhammad Rohady Ramadhan; Muhammad Rais Rahmat (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
The study aims to find out how the implementation of Accountibility and transparency in the Covid 19 pandemic in Lagading Village, Pitu Riase District, Sidenreng rappang Regency.The population in this study was 404 households where the sampling used was Incidental Sampling Incidental Slovin formula. The error rate was 10% with a sample size of 80 Households.This study uses descriptive quantitative Methods.Data collection techniques used are through observation, questionnaires, interviews and Literature study. The Results of this study indicate that the average Percentage of the application of Accountability and Transparency to the management of Village funds in the Lagading Village,Pitu Riase District,Sidenreng Rappang District Is 65,3 with a Good Category,and the factors that influence the application of Accountability and Transparency to the nanagement of village funds in the past.the Covid 19 pandemic is 59,3 in the doubtful Category.